Does interaction between TQM practices and knowledge management processes enhance the innovation performance? - Yusr, Maha Mohammed; Mohd Mokhtar, Sany Sanuri; Othman, Abdul Rahim; Sulaiman, Yaty (Emerald Publishing Limited, 2017)
Purpose: The purpose of this paper is to investigate the effect of applying total quality management (TQM) on enhancing knowledge management processes. It also examine the relationship between knowledge management and innovation performance in the Malaysian manufacturing sector. Design/methodology/approach: This study used a survey method to test the formulated hypotheses. Therefore, the adopted questionnaire was used as an instrument to collect the needed data. The population of the study consisted of 800 big and medium manufacturing companies listed in Federation of Malaysian Manufacturers (2012). Findings: The results of this paper support a positive and significant impact of TQM practice on knowledge management processes. Furthermore, the relationship between knowledge management and innovation performance has been a proved. However, further analysis on dimension level indicates that knowledge acquisition failed to show significant relationship with innovation performance Originality/value: This study addresses one of the recent issues within the Malaysian context of becoming a developed nation, which is innovation performance, specifically for manufacturing companies. To do so, the overlapping relationships among TQM practices, knowledge management, and innovation performance have been tested.